INVESTMENTS IN SERBIAN AGRICULTURE - Milić, Dragan; Jocić, Bogdan; Novaković, Tihomir; Tekić, Dragana; Ilić, Zoran; Maksimović, Branka (Economics of Agriculture, 2023)
The paper shows the relation between gross domestic product (GDP) and investments in the Republic of Serbia. The observed relation was analyzed at the economy level, as well as in agricultural particular. The observation period is from 2005 to 2020. The function of investments is overviewed through the capital ratio. In this way, it was established to what extent part of the newly created value is returned to the production process, both at the level of the entire economy and at the level of agricultural activity separately. The low participation of investments in the gross domestic product is highlighted, which indicates an unfavorable relationship towards economic and agricultural activity for the observed time period.